Development of a psychosocial group intervention for individuals with mild cognitive impairment (innovative practice). (May 2020) - Barton, Karen; Johnson, Ian; Mountford, Amy
A diagnosis of mild cognitive impairment is associated with an increase in anxiety and depression and a decrease in psychological well-being. Despite this, individuals with mild cognitive impairment may not receive the appropriate support needed to manage the emotional and practical elements of their diagnosis. A psychosocial group intervention based on the 'Recovery Model' was developed in order to meet these needs. Outcome data from a trial of this group intervention indicated it was successful in meeting its aims.